On Tetrafluorobromates(III): Crystal Structures of the Dibromate CsBr2F7 and the Monobromate CsBrF41. Issue 15 (6th August 2013) - Ivlev, Sergey; Woidy, Patrick; Sobolev, Vasily; Gerin, Ivan; Ostvald, Roman; Kraus, Florian
Abstract Alkali and alkaline earth metal tetrafluorobromates MIBrF4, MII(BrF4)2 (MI = Na–Cs, MII = Sr, Ba) can be synthesized from the respective fluorides and BrF3. By the reaction of CsF with an excess of BrF3, the compound cesium tetrafluoridobromate(III) bromine trifluoride (1/1), CsBr2F7 (1), was obtained in the form of a colorless powder and as single crystals. Shown by X‐ray diffraction on single crystals, its Br2F7– anion is neither planar, nor is its Br–μ‐F–Br unit linear, as previously deduced by Raman spectroscopy. In stoichiometric reactions of CsF with BrF3, the compound cesium tetrafluoridobromate(III), CsBrF4 (2), was obtained as a colorless powder. Compound 2 can also be obtained from compound 1 by evacuation. The crystal structure of CsBrF4 (2) was elucidated by Rietveld refinement on its X‐ray powder pattern. Its structure is not isotypic to MBrF4 (M = Na, K, Rb, NO) but isotypic to CsAuF4. CsBr2F7 is, however, not isostructural to CsAu2F7.